Dietary sugars and lipid metabolism in humans. - Frayn, K; Kingman, S (1995)
When large amounts of sugars are included in the diets of humans and other animals, alterations in concentrations of plasma lipid constituents may be observed; usually elevation of triacylglycerol concentrations and sometimes elevation of low-density-lipoprotein cholesterol and depression of high-density-lipoprotein cholesterol. These effects are not seen with amounts of sugars typical of those in the Western diet, although more information is needed on postprandial triacylglycerol concentrations, which may be affected more readily than fasting concentrations. The elevation of triacylglycerol concentrations appears to reflect both increased hepatic very-low-density-lipoprotein triacylglycerol secretion and impaired clearance. Some people are more responsive to these effects of dietary sugars than are others. Perhaps surprisingly, in many studies people with diabetes mellitus, either insulin dependent or non-insulin dependent, seem to be protected from alterations in plasma lipid concentrations brought about by large amounts of dietary sugars.